Nickel Boride Catalyzed Reductions of Nitro Compounds and Azides: Nanocellulose-Supported Catalysts in Tandem Reactions - Proietti, Giampiero; Prathap, Kaniraj Jeya; Ye, Xinchen; Olsson, Richard T.; Dinér, Peter (Synthesis, 2021)
Nickel boride catalyst prepared in situ from NiCl2 and sodium borohydride allowed, in the presence of an aqueous solution of TEMPO-oxidized nanocellulose (0.01 wt%), the reduction of a wide range of nitroarenes and aliphatic nitro compounds. Here we describe how the modified nanocellulose has a stabilizing effect on the catalyst that enables low loading of the nickel salt pre-catalyst. Ni-B prepared in situ from a methanolic solution was also used to develop a greener and facile reduction of organic azides, offering a substantially lowered catalyst loading with respect to reported methods in the literature. Both aromatic and aliphatic azides were reduced, and the protocol is compatible with a one-pot Boc-protection of the obtained amine yielding the corresponding carbamates. Finally, bacterial crystalline nanocellulose was chosen as a support for the Ni-B catalyst to allow an easy recovery step of the catalyst and its recyclability for new reduction cycles.
Keywords: Ni-B; nickel boride; nitro reduction; azide reduction; nickel boride catalyzed hydrogenation; TEMPO nanocellulose; crystalline nanocellulose